The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.schres.2019.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical health multimorbidity with mortality in people with schizophrenia spectrum disorders: Using a novel semantic search system that captures physical diseases in electronic patient records

Abstract: Association of physical health multimorbidity with mortality in people with schizophrenia spectrum disorders: Using a novel semantic search system that captures physical diseases in electronic patient records

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…The large sample size of this study, and representativeness of data from CPRD(34, 35), suggests the results of this study are generalisable to the UK population. The prevalence of multimorbidity in the SMI cohort was similar to previous studies(16, 18, 56), however prevalence of multimorbidity depends on the conditions studied and therefore other studies have found substantially different(15, 17) estimates. As with all studies using electronic health records, a limitation of this study is potential biases in recording variables.…”
Section: Discussionsupporting
confidence: 86%
“…The large sample size of this study, and representativeness of data from CPRD(34, 35), suggests the results of this study are generalisable to the UK population. The prevalence of multimorbidity in the SMI cohort was similar to previous studies(16, 18, 56), however prevalence of multimorbidity depends on the conditions studied and therefore other studies have found substantially different(15, 17) estimates. As with all studies using electronic health records, a limitation of this study is potential biases in recording variables.…”
Section: Discussionsupporting
confidence: 86%
“…However, due to the small numbers included in the affective psychotic disorder group, results pertaining to this group should be interpreted with caution. A recent report had found that cardiovascular, neurological, or skin-related diseases, each combined with respiratory diseases, had the highest impact on mortality rates [ 50 ]. As respiratory and skin conditions were reported in a sizable proportion of individuals, and as respiratory and skin conditions were significantly correlated locally, our findings, together with other evidences found overseas, would warrant a thorough examination of local data of these combinations in psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Unnatural causes of death, i.e., suicide, accidents, and homicide, considerably contribute to this disparity [3], yet chronic somatic health conditions account for the majority of lost life years among people with SMI [4]. The majority of deaths are due to cardiovascular disease, respiratory disease, and cancer [5][6][7][8][9]. People with SMI are at higher risk of several chronic somatic conditions, particularly cardiovascular diseases [10], diabetes mellitus type II [11], metabolic syndrome [12], respiratory diseases, and liver abnormalities [13] as well as the risk of somatic multimorbidity [9].…”
Section: Background and Rationalementioning
confidence: 99%
“…The majority of deaths are due to cardiovascular disease, respiratory disease, and cancer [5][6][7][8][9]. People with SMI are at higher risk of several chronic somatic conditions, particularly cardiovascular diseases [10], diabetes mellitus type II [11], metabolic syndrome [12], respiratory diseases, and liver abnormalities [13] as well as the risk of somatic multimorbidity [9]. The mechanisms connecting SMI and somatic conditions are complex.…”
Section: Background and Rationalementioning
confidence: 99%